Reconstruction Of Policy Arrangements For The Regulation Of Mining Business Licenses For The Sale Of Marine Sedimentation Products In The Perspective Of Environmental Administration Law - Indra Lorenly Nainggolan, Indra Lorenly Nainggolan; Nina Zainab, Nina Zainab; Rona Apriana Fajarwati, Rona Apriana Fajarwati (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The results of deep sea sedimentation PP No. 26 of 2023 concerning the management of sedimentation products in the sea have provided space for mining business permits for sale. Mining business licenses for sale from the perspective of environmental administration law must be placed in the provisions of article 28H paragraph 1 of the 1945 Constitution of the Republic of Indonesia, especially regarding a good and healthy environment. Is the management of marine sedimentation products for reclamation using mining business license instruments for sale in accordance with the legal values of environmental administration as stipulated in article 28H paragraph 1 of the 1945 Constitution of the Republic of Indonesia? The research method used is normative juridical, by analyzing laws and regulations using a conceptual approach. The results of the study found that the concept of mining business licenses for sale in Government Regulation No. 26 of 2023 is not in line with the principles of a good and healthy environment. A good and healthy environment is a guarantee for all people to participate fully, providing a sense of concern for environmental protection. Furthermore, mining business permits for sale are indeed intended for the economic interests of business actors, because the final form of management of sedimentation products in the sea is indeed prioritized to obtain profits. An increase in the added value of the community's economy will never be achieved in Government Regulation No. 26 of 2023. This makes the principle of special rights and the right to development for the general public, related to the guarantee of free and complete participation of indigenous peoples, will be ignored